Discriminated conditioned suppression in rats - Ribeiro,Thais Arantes (2012)
This experiment evaluated the effects of superimposing the Estes-Skinner Conditioned Emotional Response (CER) procedure on one of two components of a multiple schedule. The question was whether CER conditioning occurred under contextual control. The procedure had four experimental phases: (1) baseline of operant responding under a two-component multiple schedule (mult VI 30 VI 30), one component correlated with the house light on and the other correlated with the house light off (light/dark components), (2) introduction of tone-shock pairings during the light component only, (3) return to baseline contingencies, and (4) reintroduction of the tone (but not shock) in the light component. Three Wistar rats showed robust suppression of responding in the light component, and the suppression also partially generalized to the dark component. The suppression was stronger during the pre-aversive stimulus than during the intervals immediately before and after its presentation. Responding partially recovered under baseline contingencies, but response rates remained lower in the light component than in the dark component. Thus, under the present experimental conditions, the context in which CER conditioning occurred (i.e., the house light-illuminated chamber) also produced conditioned suppression, and contextual control of suppressed responding generalized to another context, one that shared some but not all elements of the first context (i.e., the same chamber not illuminated by a house light). These results have direct implications for our understanding of emotional conditioning produced in the laboratory and for analysis of related phenomena addressed in the clinic.